Mucocutaneous Manifestations and Association with Clinico-Immunological Categories, CD4 Indices, and ART Adherence in HIV-Infected Children in Umuahia, South-East Nigeria - Odochi Ewurum; Ihuoma K. Ukpabi; Thomas O. Nnaji; Ngozi C. Ojinnaka (International Journal of Medicine and Health Development)
Background: Mucocutaneous disorders are indicators of human immunodeficiency virus (HIV)/AIDS, and correlation with clinical and immunological categories of the patients may serve as a guide for management in poor-resource countries. Objectives: To determine the association between mucocutaneous manifestations in HIV-infected children in Umuahia and the clinical and immunological categories, CD4 indices, and antiretroviral therapy (ART) adherence. Materials and Methods: A descriptive, cross-sectional, and comparative study, carried out on 120 children with HIV infection, aged 4 months to 15 years who were consecutively recruited in the pediatric HIV clinic. Detailed clinical information was collected; World Health Organization (WHO) pediatric clinical staging and classification of HIV-associated immunodeficiency was used for clinico-immunological categories. Mucocutaneous lesion was diagnosed clinically. Skin scrapings and biopsy were carried out to confirm the diagnosis. Statistical Package for Social Sciences (SPSS) version 20 was used. The chi-square test was used for categorical variables, and the Student t-test was used as appropriate. P value < 0.05 was considered statistically significant. Results: Mucocutaneous manifestations occurred in 67 (55.8%) children and non-infective in 35 (52.2%). They were most common among children with severe immunosuppression (74.1%) and those in clinical stage 2 (98.5%). The differences in mean CD4 count and percentage of those with and without mucocutaneous lesions were statistically significant (t = 4.37, P < 0.001 and t = 8.83, P < 0.001, respectively). Children with non-infective lesions had severe immunosuppression. All patients in clinical stage 3 had an infective lesion. Mucocutaneous lesions were very common, occurring in 81.3% of those not on ART and 58.6% not adherent to medications. Conclusions: The severity of the mucocutaneous manifestation increased with worsening immune status of patients. Strict monitoring of adherence to ART is highly advocated.